The effects of mindfulness training on weight-loss and health-related behaviours in adults with overweight and obesity: A systematic review and meta-analysis. Issue 1 (September 2017) - Ruffault, Alexis; Czernichow, Sébastien; Hagger, Martin S.; Ferrand, Margot; Erichot, Nelly; Carette, Claire; Boujut, Emilie; Flahault, Cécile
Highlights: Mindfulness training has been related to the adoption of healthier behaviours. We conducted a meta-analysis of RCTs testing mindfulness training for weight loss. Mindfulness decreases binge and impulsive eating and increases physical activity. No effects of mindfulness training on weight loss in adults with excess weight. Study design is a major source of heterogeneity in study effects. Summary: The aim of this study was to conduct a comprehensive quantitative synthesis of the effects of mindfulness training interventions on weight-loss and health behaviours in adults with overweight and obesity using meta-analytic techniques. Studies included in the analysis ( k  = 12) were randomised controlled trials investigating the effects of any form of mindfulness training on weight loss, impulsive eating, binge eating, or physical activity participation in adults with overweight and obesity. Random effects meta-analysis revealed that mindfulness training had no significant effect on weight loss, but an overall negative effect on impulsive eating ( d  = −1.13) and binge eating ( d  = −.90), and a positive effect on physical activity levels ( d  = .42). Meta-regression analysis showed that methodological features of included studies accounted for 100% of statistical heterogeneity of the effects of mindfulness training on weight loss ( R 2  = 1, 00). Among methodological features, the only significant predictor of weight loss was follow-up distance from post-intervention ( β  = 1.18; p  < .05), suggesting that the longer follow-up distances were associated with greater weight loss. Results suggest that mindfulness training has short-term benefits on health-related behaviours. Future studies should explore the effectiveness of mindfulness training on long-term post-intervention weight loss in adults with overweight and obesity.